(untitled) (Medicinski podmladak, 2022)
Introduction: Patients with myocardial infarction who are effectively treated with primary percutaneous coronary intervention (PCI) may have significant coronary artery stenosis that is not responsible for current myocardial infarction. Non-infarction artery stenosis can cause serious adverse cardiac events, which can be avoided by performing PCI. Coronary flow reserve (CFR) is defined as the ratio of the hyperemic mean blood flow velocity to the resting blood flow velocity for a given coronary artery. CFR decreases with increasing severity of the lesion. Aim: The aim of this study was to determine the prognostic value of CFR determined by transthoracic Doppler echocardiographic flow evaluation, in the coronary artery, in patients with residual intermediate stenosis of the non-infarcted artery after PCI. Material and methods: The prospective study included 106 patients treated at the Clinical Center of Serbia in the period of July 2007 to December 2014. CFR was performed on a non-infarcted coronary artery with intermediate stenosis (40-70%). Adenosine was administered intravenously for two minutes to induce hyperemia at a dose of 140 mcg/kg/min. CFR was calculated as the ratio of the maximum diastolic flow rate under hyperemia and the maximum flow rate under basal conditions. Patients were invited for follow-up at 6, 12, 18, and 24 months to determine the occurrence of composite adverse events, which included: cardiac death, stroke, myocardial infarction, and myocardial revascularization (non-infarction lesion). Results: There were 7 (6.6%) anterior infarcts in the sample, 13 lateral infarcts (12.3%), and 86 inferior-posterior (81.1%). 69 (65%) subjects were diagnosed with one-vessel coronary heart disease, 33 (31%) had two-vessel disease, and 4 (4%) patients were diagnosed with three-vessel disease. In our group of patients, 18 adverse events were reported during follow-up. A statistically highly significant difference (p <0.001) in CFR values was found in patients with adverse events compared to patients without adverse events. The CFR>2 value had a high negative predictive value (95%) for the absence of adverse events. Conclusion: In patients with CFR> 2, revascularization can be safely delayed with continued optimal drug therapy. Non-invasive transthoracic Doppler CFR is a cheap and safe method that enables serial and repeated monitoring of the functional significance of stenosis on the "non-infarction" coronary artery.